An accurate imaging and doppler chirp rate estimation algorithm for airborne CSSAR-GMTI systems - Li, Yongkang (2021)
Airborne circular stripmap synthetic aperture radar (CSSAR)-ground moving target indication (GMTI) systems are attractive tools for air-to-ground surveillance and monitoring, because of their advantages of short revisit time and large coverage. This paper proposes an accurate imaging and Doppler chirp rate estimation algorithm for the airborne CSSAR-GMTI system with high range resolution. A key step of this algorithm is to utilize an alternation strategy to implement the correction of the target's range cell migration and the estimation of the range equation's quadratic coefficient alternatively. This step enables the proposed algorithm to achieve an accurate imaging and Doppler chirp rate estimation of a ground moving target. In addition, this paper presents an investigation on the accuracy of the quadratic-approximated range equation for ground moving target imaging. Numerical experiments are conducted to validate the proposed algorithm.